INTERNALISASI KODE ETIK BIMBINGAN DAN KONSELING INDONESIA PADA MAHASISWA BIMBINGAN DAN KONSELING - Agus Basuki; Moh Farozin; Ismarini Bekti Setiani (Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to obtain empirical data about the level of internalization of the code of ethics for guidance and counseling in general, based on the internalization stage, and by gender in guidance and counseling students at Yogyakarta State University. The study was designed over a period of 6 months using a quantitative approach, with a descriptive research type. The sampling technique used purposive sampling, namely 71 students who have internalized the code of ethics of guidance and counseling through guidance and counseling professional orientation lectures